The blurring dots between illusion and reality in film : a metamorphosis / Maszalida Hamzah - Hamzah, Maszalida (UPENA, 2006)
Often times, film, infect us with its narrative, awe inspiring characters, visual landscapes and its real life mimicry. While acknowledging this animated 'stills', the conscious mind is in transit, subconsciously forming a 'contract' with .the powerful medium of film. They feel, taste, savour and react to the moments, intermingling both joy and suffering as if it is their very own. To Tolstoy, 'a real work of art destroys, in the consciousness of the receiver, the separation between himself and the artist'. Could this be the moment when the reality-illusion partnership is annihilated? Thus, film is in itself, a mode of elevated existence, unconsciously imprisoning and consciously freeing. The knowledge of this powerful art (film) and the impact it brings must be researched as no art can escape truth, beauty, significance and its encounter with the Real. This essay attempts to locate the interspace between reality and illusion in film; translating its seemingly blurring 'dots' as an identifiable manifestation, in the hopes of grasping the unity behind the trinity of reality-dot-illusion in film.